PENYULUHAN MENGENAI BAHAYA PENGGUNAAN BABY WALKER DI POSYANDU KIDUL DALEM RW 4 KOTA MALANG - Prasasti Millennia Seputri; Nikmatur Rosidah (LPPM Universitas Abdurrab, 2024)
Baby walkers are promoted to parents as tools that can help children learn to walk. However, research shows that this is not true. Baby walkers have been shown to slow gross motor skills and increase the incidence of injuries. This counseling was conducted with the aim of providing education to parents, especially mothers who often accompany children in health post activities regarding the dangers of using baby walkers. The counseling method uses leaflet media and there is a pretest and post-test by giving a questionnaire containing several questions about baby walkers to assess the effectiveness of counseling. The evaluation results showed an increase in knowledge with a value of 97.5% of respondents able to answer perfectly and only 2.5% who could not answer the question perfectly. This value shows that counseling on the dangers of using baby walkers has the effectiveness of increasing parents' knowledge about the effects of using baby walkers on children's motor development. In this case, the risk of children's motor development problems can be avoided.